Peran Indoor Environmental Quality terhadap Psychological Well-Being Penghuni Rusun Penjaringan Sari III Surabaya - Nilamsari, Pranedia; Tjahjoanggoro, A. J.; Tondok, Marselius Sampe (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
By using the ergonomic concept, the physical environment of a residence’s inhabitant, namely indoor environmental quality (IEQ), becomes one of the determinants of its inhabitant’s psychological state. However, there are still limited previous studies examining the IEQ and its elements such as thermal comfort, acoustic comfort, indoor air quality, and visual comfort in small housing settings and its role on the psychological condition of its occupants, namely psychological well-being (PWB). However, there are still limited previous studies examining the IEQ in small housing settings and its role on PWB of its inhabitants. This study aimed to determine and explain the role of IEQ and its aspects on PWB of small housing inhabitants. This quantitative survey research used questionnaire as the main data collection and supported by interviews and observations. The participants of this study were 90 residents of the flat, representing the occupants of the unit, which were selected by random sampling technique from the 112 occupied units. Simple regression analysis was used to test the research hypothesis. The results showed that the quality of the environment in the dwelling had a significant positive role on PWB of the small house inhabitants (R = 0.272; R2 = 0.074; p <0.05) by 7.4%. Among the four aspects of EIQ, there were two aspects that played a significant role on PWB, namely air quality and temperature. This study also revealed that majority of the participants had PWB in the high category, and IEQ in the medium category. Moreover, the ability of residents to adapt and change the environment were considered as psychological factors that influence the small housing inhabitant’s interaction toward indoor physical environment.